Could Lipoprotein Lipase Play a Role in Alzheimer's Disease?. (2004) - Blain, Jean-Francois; Poirier, Judes
Abstract : This paper reviews recent literature on the role of lipoprotein lipase in the central nervous system with a focus on its recently described role in synaptic remodeling. This novel role could have implication for Alzheimer's disease treatment.